A study on the trend of cloud service and security through text mining technique - Taek Park, Seong; Won Lee, Sung; Gu Kang, Tae (International Journal of Engineering and Technology, 2018)
Background/Objectives: The purpose of this study is to recognize the significance of security of cloud service activation and success and to draw the direction and importance for the development of Korean cloud service. Cloud computing service makes it possible to conduct a test easily and quickly at a low cost, to be scalable with an inexpensive cost, and to curb unnecessary expenses.Methods/Statistical analysis: This study collected news articles from NAVER with the use of crawling technique. The collected data were pre-processed (cleaned), and then 25 words with a high priority were analyzed in the category of the first half of 2015, the second half of 2015, and the first half of 2016.Findings: To find the trend of cloud computing service security, this study collected news articles and analyzed them after data cleaning. The analysis revealed that there was a difference in importance of each period. In the first half of 2015, the 2nd half of 2015, and the 1st half of 2016, the common noun words extracted were cloud, service, security, and enterprise in order.The difference was that the word 'environment' was found in the 1st half of 2015, the word 'management' in the 2nd half of 2015, and the words 'customer' and 'use' in the 1st half of 2016.Improvements/Applications: According to the analysis, there was a difference in importance by year. It is considered that the study results will be able to serve as the guidelines for establishing a systematic plan of cloud service security in the firms and institutions providing cloud service.Â Â